KRITIK MATN SEBAGAI METODE UTAMA DALAM PENELITIAN KESAHIHAN HADIS NABI - Khabibi Muhammad Luthfi (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2015)
The research method was dominated critiques hadith sanad, so criticism of honor is considered as a complementary method, whereas honor is the substance of the tradition itself, which was initially used as a consideration in determining the quality of the hadith. On this basis, this article tried to put kririk honor as the primary method in the study of hadith. By using the approach of 'ulu> m al- Hadi> s {via the method of literature found that criticism of honor has rules that can scientifically be used as the primary method, or at least parallel to ktirik sanan. In addition, criticism of honor which historically suspended animation, at this time began to be revived. One of the main motivations is some correlation and similarity of the contents of the hadith with the knowledge produced by modern sciences.